2013
DOI: 10.1007/s11356-013-1610-4
|View full text |Cite
|
Sign up to set email alerts
|

Using iron-loaded sepiolite obtained by adsorption as a catalyst in the electro-Fenton oxidation of Reactive Black 5

Abstract: This study explores the possibility of using iron-loaded sepiolite, obtained by recovering iron from polluted water, as a catalyst in the electro-Fenton oxidation of organic pollutants in textile effluents. The removal of iron ions from aqueous solution by adsorption on sepiolite was studied in batch tests at iron concentrations between 100 and 1,000 ppm. Electro-Fenton experiments were carried out in an electrochemical cell with a working volume of 0.15 L, an air flow of 1 L/min, and 3 g of iron-loaded sepiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 67 publications
3
25
0
4
Order By: Relevance
“…RB5 has been chosen as a model organic pollutant by a number of researchers, and details are available concerning degradation of the dye by electro-assisted Fenton and Fentonlike oxidation [4,[22][23][24][25], photo-electrochemical [26,27] and electro-coagulation [28] processes, electrochemical reduction [29][30][31][32], and electrochemical oxidation with Ti/SnO2-SbPt [3], Pt [33], graphite [34] and Pt/Ti [35] electrodes. However, very few studies have focused on the application of BDD as electrodic material for the removal of RB5.…”
Section: [Figure 1 Near Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…RB5 has been chosen as a model organic pollutant by a number of researchers, and details are available concerning degradation of the dye by electro-assisted Fenton and Fentonlike oxidation [4,[22][23][24][25], photo-electrochemical [26,27] and electro-coagulation [28] processes, electrochemical reduction [29][30][31][32], and electrochemical oxidation with Ti/SnO2-SbPt [3], Pt [33], graphite [34] and Pt/Ti [35] electrodes. However, very few studies have focused on the application of BDD as electrodic material for the removal of RB5.…”
Section: [Figure 1 Near Here]mentioning
confidence: 99%
“…However, very few studies have focused on the application of BDD as electrodic material for the removal of RB5. For example, Iglesias et al [22] investigated the removal of RB5 by the electro-Fenton process using a BDD anode and graphite sheet cathode and reported that 97.2% of color was removed after 90 min of electrolysis at 5 V applied potential. Additionally, electro-oxidation of RB5…”
Section: [Figure 1 Near Here]mentioning
confidence: 99%
“…A suitable low-cost adsorbent requires a porous structure, mechanical and chemical stability and affinity for the target pollutants (Cobas et al, 2014). Recent the utilisation of non-conventional adsorbents; natural clays (Iglesias et al, 2013;Padilla-Ortega et al, 2013), various industrial and agricultural materials such as hazelnut straws, peanut shell, banana peel, orange peel, walnut shell, rice husk and sawdust (Nguyen et al, 2013;Alothman et al, 2013;Ma et al, 2014;Park et al, 2008;Krishnani et al, 2008;Abdolali et al, 2014a) and forestry materials such as fern or oak leaves (Prasad and Freitas, 2000;Barriada et al, 2009) have been tested. These agroforestry materials have been mainly applied to the removal of a single or a couple of metals, while little attention has been paid to the simultaneous adsorption of multiple metals (Krishnani et al, 2008;Abdolali et al, 2014b;Hossain et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…EF processes have been used to degrade RB-5 using anode and cathode graphite electrodes of 84.16 cm 2 area [28]. Glassy carbon electrodes also have been used [29] as well as graphite (area 15 cm 2 ) and Fe alginate gel beads and iron-loaded sepiolite [30,31]. Bocos et al used two graphite sheets electrodes of 15 cm 2 area and an iron supported in polyacrylamide hydrogel [32].…”
Section: Introductionmentioning
confidence: 99%